Good governance in strategic planning of local development in rural and urban-rural gminas of the eastern peripheral voivodeships of Poland - Guzal-Dec Danuta; Zbucki Łukasz; Kuś Agnieszka (Bulletin of Geography. Socio-Economic Series)
The work aimed to determine the scope of the good governance approach in the local development planning of local governments of rural and urban-rural gminas in the eastern peripheral voivodeships of Poland (Lubelskie, Podlaskie and Świętokrzyskie Voivodeships) and how the implementation of good governance principles in the process of elaborating and implementing local development strategies correlates with assessments of the strategy's suitability as a development management tool. The research used methods of analysis and criticism of the literature, statistical analysis and a survey method using an interview questionnaire addressed to local government authorities. According to our research, especially at the stage of developing the strategy, actions were taken regarding local-community and local-authority participation and active communication between the two, but a lower level of community participation was found at the implementation stage. There was a statistically significant relationship between adopting the principle of participation and accountability in preparing and implementing the strategy and how suitable the strategy was assessed to be as a tool for development management. It seems reasonable to apply the principles of good governance more widely in planning local development, not only while developing the strategy, but also in its implementation.